2016
DOI: 10.1128/jvi.03223-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Norovirus Inhibition by Human Milk Oligosaccharides

Abstract: dHisto-blood group antigens (HBGAs) are important binding factors for norovirus infections. We show that two human milk oligosaccharides, 2=-fucosyllactose (2=FL) and 3-fucosyllactose (3FL), could block norovirus from binding to surrogate HBGA samples. We found that 2=FL and 3FL bound at the equivalent HBGA pockets on the norovirus capsid using X-ray crystallography. Our data revealed that 2=FL and 3FL structurally mimic HBGAs. These results suggest that 2=FL and 3FL might act as naturally occurring decoys in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 27 publications
1
129
1
2
Order By: Relevance
“…In addition, FUT2 functionality has been linked to infection with rotavirus, another enteric pathogen that causes diarrheal disease in children, and that utilizes cell surface carbohydrates for attachment (114). These results provide a basis for identifying individuals resistant to infection by these viruses and suggest that the development of purified fucose-containing oligosaccharides may be effective as anti-infectives (163). …”
Section: Norovirus and Rotavirusmentioning
confidence: 93%
“…In addition, FUT2 functionality has been linked to infection with rotavirus, another enteric pathogen that causes diarrheal disease in children, and that utilizes cell surface carbohydrates for attachment (114). These results provide a basis for identifying individuals resistant to infection by these viruses and suggest that the development of purified fucose-containing oligosaccharides may be effective as anti-infectives (163). …”
Section: Norovirus and Rotavirusmentioning
confidence: 93%
“…Several studies showed that human milk or HMOs could compete with the HBGA binding sites on the norovirus capsid (27,28). We recently showed that two HMOs, 2=FL and 3FL, blocked norovirus from binding to HBGAs in a mostly dose-dependent manner (29). HMOs can resist degradation in the gut, and the majority is excreted intact in the feces (Ďł1% is absorbed by the infant).…”
Section: Human Norovirus and Hmosmentioning
confidence: 99%
“…The HMO binding site on the GII.10 capsid was recently discovered (29). The 2=FL and 3FL bound at the equivalent HBGA pocket on the norovirus capsid (Fig.…”
Section: Structural Basis For Norovirus Binding To Hmosmentioning
confidence: 99%
“…Pig gastric mucin (PGM) and saliva blocking assays were performed as previously described [69]. Briefly, ELISA plates were coated with 10 Îźg/ml PGM (Sigma, Germany) or with saliva type A or B diluted in PBS 1:2000.…”
Section: Blocking Assaysmentioning
confidence: 99%